PERSIST: Physician’s Evaluation of Restasis(®) Satisfaction in Second Trial of topical cyclosporine ophthalmic emulsion 0.05% for dry eye: a retrospective review - Mah, Francis (Dove Medical Press, 2012)
BACKGROUND: Chronic dry eye disease often requires long-term therapy. Tear film alterations in the setting of dry eye may include reduced tear volume as well as an increase in inflammatory cytokines and osmolarity. Topical cyclosporine ophthalmic emulsion 0.05% (Restasis(®); Allergan Inc, Irvine, CA) is indicated to increase tear production in patients with dry eye and reduced tear production presumed to be due to ocular inflammation. This study was designed to evaluate the efficacy of a second trial of topical cyclosporine in patients with dry eye who were previously considered treatment failures. MATERIALS AND METHODS: This multicenter (three cornea practices) retrospective chart review evaluated clinical outcomes in patients with dry eye who received a second trial of cyclosporine after a prior treatment failure, defined as prior discontinuation of topical cyclosporine after less than 12 weeks. RESULTS: Thirty-five patients, most of whom were female (71.4%) and Caucasian (62.9%), were identified. Prior discontinuation was most commonly due to burning/stinging (60%). The median duration of second treatment was 10 months (range 1 week to 45 months). Physician education was provided in the second trial in 97.1% of cases. At initiation of the second trial of cyclosporine, 10 (28.6%) patients received courses of topical corticosteroids. Physicians reported on a questionnaire that 80% of patients achieved clinical benefit with a second trial of cyclosporine. CONCLUSION: A repeat trial with topical cyclosporine can achieve clinical success. Direct patient education via the physician and staff may be key to success. Proper patient education may overcome adherence issues, particularly with respect to the need for long-term treatment of chronic dry eye. This study has the usual limitations associated with a retrospective chart review, and future prospective studies are warranted.